Long‐distance dispersal in a fire‐ and livestock‐protected savanna. Issue 4 (7th March 2013) - Tarazi, Roberto; Sebbenn, Alexandre M.; Kageyama, Paulo Y.; Vencovsky, Roland
Abstract Savannas are highly diverse and dynamic environments that can shift to forest formations due to protection policies. Long‐distance dispersal may shape the genetic structure of these new closed forest formations. We analyzed eight microsatellite loci using a single‐time approach to understand contemporary pollen and effective seed dispersal of the tropical tree, Copaifera langsdorffii Desf. (Fabaceae), occurring in a Brazilian fire‐ and livestock‐protected savanna. We sampled all adult trees found within a 10.24 ha permanent plot, young trees within a subplot of 1.44 ha and open‐pollinated seeds. We detected a very high level of genetic diversity among the three generations in the studied plot. Parentage analysis revealed high pollen immigration rate (0.64) and a mean contemporary pollen dispersal distance of 74 m. In addition, half‐sib production was 1.8 times higher than full‐sibs in significant higher distances, indicating foraging activity preference for different trees at long distances. There was a significant and negative correlation between diameter at breast height (DBH) of the pollen donor with the number of seeds (r = −0.640, P‐value = 0.032), suggesting that pollen donor trees with a higher DBH produce less seeds. The mean distance of realized seed dispersal (recruitment kernel) was 135 m due to the large home range dispersers (birds and mammals) in the area. The small magnitude of spatial genetic structure found in young trees may be a consequence of overlapping seed shadows and increased tree density. Our results show the positive side of closed canopy expansion, where animal activities regarding pollination and seed dispersal are extremely high.